Pembuktian Mukzizat para Nabi dalam Sains Modern Menurut Maulana Muhammad Ali dan Quraish Shihab: Studi Komparatif Tafsir Al-Misbah dan Tafsir The Holy Qur’an - Nabila, Divia; Kurnia Shofa, Ida; Muallim, Mohamad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Miracles are extraordinary events given by God to prophets to prove their prophethood. In general, something extraordinary becomes unreasonable and irrational. In the history of interpretation regarding the verses of miracles experienced many changes from the early period to the present. For example, the modern century mufassir, Maulana Muhammad Ali and contemporary mufassir, M. Quraish Shihab have differences in interpreting the verses of miracles even though they both use bi al-ra'yi interpretation. If the Qur'an has an absolute dimension and is absolute, on the contrary, modern knowledge is dynamic and changes along with scientific discoveries. So this research will focus on the comparison of Maulana Muhammad Ali and Quraish Shihab in interpreting the verses of miracles through modern science. The type of research used is Library Research (library research) and the method used is qualitative with a descriptive-comparative approach.